Celebrating Indigenous Culture and Identity in Bapsi Sidhwa’s Ice Candy Man: A Postcolonial Critique - Zahid Abbas (University of Chitral Journal of Linguistics and Literature, 2023)
To justify colonialism and perpetuate colonial rule the colonizers appropriated their political, cultural, academic, literary, and linguistic supremacy which left a tinge of mimicry and hybridity among the natives. The colonizers, being in the centre, employed colonial discourse, Eurocentric historic construct, Western education system, English language, missionary and creative literature to portray the periphery, the colonized, as uncivilized, accultured, incompetent, uncouth and diabolical evils. To rebut this, the postcolonial writers rejected colonialist ideology and cultural supremacy by asserting native culture, identity, language, and societal values. They disassociated themselves from cultural imperialism and celebrated their indigenous culture. This study analyses the portrayal of celebration of the indigenous culture and identity in Bapsi Sidhwa’s novel Ice Candy Man (1988-89) from the vantage point of postcolonial theory. It has been found that Sidhwa celebrates indigenous culture, identity, tradition, language, and localization in the novel. To this effect, she employs code-mixing to add indigenous semantics, delineates characters from the locality, asserts her Pakistaniness and objectifies Pakistani leadership and narrative in the novel and thus she continues to live as a postcolonial writer.